Spatial Distribution of the Eddy Diffusion Coefficients in the Plasma Sheet During Quiet Time and Substorms from Themis Satellite Data - Stepanova, M (Blackwell Publishing Ltd, 2011)
During the last decade, a number of studies have shown that turbulent processes in the plasma sheet are very important for the analysis of the formation of quasi-stable plasma sheet configurations. The existence of this turbulence provides a self-consistent approach to study the dynamics of the Earth s magnetosphere, including the plasma sheet stability. The turbulence can also be very important for an understanding of the location of an isolated substorm expansion phase onset. In this study the level of turbulence has been evaluated by calculating the eddy diffusion coefficients using the Time History of Events and Macroscale Interactions during Substorms satellite data. It was found that the value of the eddy diffusion coefficients may vary by at least 3 orders of magnitude, generally ranging from 103 to 106 km2/s, increasing with the distance from the Earth. The area of low eddy diffusion coefficients, less than 104 km2/s, is situated at distances below 12 RE in the tail where we found the transition region between the dipole and the tail-like geomagnetic field configuration. This region is consistent with the location of isolated substorms, as indicated by the first auroral arc brightening situated at the equatorial edge of the auroral oval. Copyright 2011 by the American Geophysical Union.